Study on the effect of chlorine on the growth of CH3NH3PbI3−xClx crystals. (20th January 2020) - Song, Tingyu; Gao, Lifeng; Wei, Qi; Yu, Limin; Wang, Shiwei; Zhang, Mingyao; Zhao, Lisha; Cai, Yanhua
Abstract: Organic-inorganic hybrid halide perovskites have attracted great interest for scientists and entrepreneurs due to their intrinsic properties and considerable business prospects in recent years. Perovskite single crystal can determine its properties well because of no grain boundaries for itself, so it is necessary to study the nucleation and growth process of perovskite crystals. In this work, CH3 NH3 PbI3−x Clx single crystals with about 10 mm sized are prepared. It's found that chlorine can restrict the nucleation and slow crystallization during the perovskite grown process. Moreover, the number of perovskite crystals can be controlled by tuning the content of chlorine in the precursor solutions, because chlorine can restrict the perovskite crystal nucleation as an inhibitor.